ANALISIS KESULITAN MEMBACA PERMULAAN PADA SISWA KELAS IIA DI SD NEGERI KEMBARAN - Lili Suwanda; Dedy Irawan (STKIP Subang, 2025)
ABSTRACT Learning barriers often faced by students in lower grades of Elementary School are difficulties in beginning reading. This problem was also found in class IIA students of Kembaran State Elementary School, which was the main focus of this study. The purpose of this study was to provide a deeper understanding of the types of beginning reading difficulties experienced by students. This study used a qualitative approach with a case study method. The subjects of the study consisted of 13 students who had difficulty reading, class IIA teachers, and 13 parents of the students. Data collection techniques were carried out through observation, interviews, and document analysis. Data validity testing was carried out using the Miles Huberman model, which includes data collection, data reduction, data presentation, and drawing conclusions. The results of the study showed that 13 students of class IIA of SD Negeri Kembaran had difficulty in beginning reading, which included: a) Difficulty in recognizing the alphabet, where 2 students did not recognize letters from A to Z, b) Difficulty in recognizing consonants, with 3 students only knowing a few consonants, c) Difficulty in reading diphthongs, where 4 students had difficulty pronouncing diphthongs or stuttered when reading them, d) Difficulty in reading words, where 4 students still spelled words when reading, e) Difficulty in reading sentences, where 13 students were not yet fluent in reading sentences. ABSTRAK Hambatan belajar yang kerap dihadapi oleh siswa di kelas rendah Sekolah Dasar adalah kesulitan dalam membaca permulaan. Masalah ini juga ditemukan pada siswa kelas IIA SD Negeri Kembaran, yang menjadi fokus utama dalam penelitian ini. Tujuan dari penelitian ini adalah untuk memberikan pemahaman lebih mendalam mengenai jenis-jenis kesulitan membaca permulaan yang dialami oleh siswa. Penelitian ini menggunakan pendekatan kualitatif dengan metode studi kasus. Subjek penelitian terdiri dari 13 siswa yang mengalami kesulitan membaca, guru kelas IIA, dan 13 orangtua siswa tersebut. Teknik pengumpulan data dilakukan melalui observasi, wawancara, dan analisis dokumen. Uji validitas data dilakukan dengan model Miles Huberman, yang meliputi pengumpulan data, reduksi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa 13 siswa kelas IIA SD Negeri Kembaran mengalami kesulitan membaca permulaan, yang meliputi: a) Kesulitan mengenal huruf alfabet, di mana 2 siswa tidak mengenal huruf dari A sampai Z, b) Kesulitan dalam mengenal huruf konsonan, dengan 3 siswa hanya mengetahui beberapa huruf konsonan, c) Kesulitan dalam membaca huruf diftong, di mana 4 siswa kesulitan mengucapkan huruf diftong atau terbata-bata saat membacanya, d) Kesulitan dalam membaca kata, di mana 4 siswa masih mengeja kata saat membaca, e) Kesulitan dalam membaca kalimat, di mana 13 siswa belum lancar dalam membaca kalimat.